In Vitro Immunomodulation of a Whole Blood IFN-γ Release Assay Enhances T Cell Responses in Subjects with Latent Tuberculosis Infection - Gaur, Rajiv L.; Suhosk, Megan M.; Banaei, Niaz (PloS one, 2012)
Activation of innate immunity via pathogen recognition receptors (PRR) modulates adaptive immune responses. PRR ligands are being exploited as vaccine adjuvants and as therapeutics, but their utility in diagnostics has not been explored. Interferon-gamma (IFN-γ) release assays (IGRAs) are functional T cell assays used to diagnose latent tuberculosis infection (LTBI); however, novel approaches are needed to improve their sensitivity. In vitro immunomodulation of a whole blood IGRA (QuantiFERON®-TB GOLD In-Tube) with Toll-like receptor agonists poly(I:C), LPS, and imiquimod was performed on blood from subjects with LTBI and negative controls. In vitro immunomodulation significantly enhanced the response of T cells stimulated with M. tuberculosis antigens from subjects with LTBI but not from uninfected controls. Immunomodulation of IGRA revealed T cell responses in subjects with LTBI whose T cells otherwise do not respond to in vitro stimulation with antigens alone. Similar to their in vivo functions, addition of poly(I:C) and LPS to whole blood induced secretion of inflammatory cytokines and IFN-α and enhanced the surface expression of antigen presenting and costimulatory molecules on antigen presenting cells. In vitro immunomodulation of whole blood IGRA may be an effective strategy for enhancing the sensitivity of T cells for diagnosis of LTBI.